2021
DOI: 10.1186/s12889-021-10833-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations of midpoint of sleep and night sleep duration with type 2 diabetes mellitus in Chinese rural population: the Henan rural cohort study

Abstract: Background The study aimed to investigate the independent and combined effects of midpoint of sleep and night sleep duration on type 2 diabetes mellitus (T2DM) in areas with limited resources. Methods A total of 37,276 participants (14,456 men and 22,820 women) were derived from the Henan Rural Cohort Study. Sleep information was assessed based on the Pittsburgh Sleep Quality Index. Logistic regression models and restricted cubic splines were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Later sleep timing has been associated with a higher risk for cardiometabolic factors in many studies [ 69 , 70 , 71 ]. However, in a rural Chinese cohort, both late and early midpoints of sleep were associated with a higher prevalence of diabetes [ 72 ], probably due to a mismatch between internal circadian rhythms and work schedule obligations in early sleepers [ 73 ]. We have shown that later sleep timing characteristics are associated with taste perception, specifically a lower bitter taste perception and TAS2R38-rs713598, and with a higher taste intensity for salty and sour tastes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later sleep timing has been associated with a higher risk for cardiometabolic factors in many studies [ 69 , 70 , 71 ]. However, in a rural Chinese cohort, both late and early midpoints of sleep were associated with a higher prevalence of diabetes [ 72 ], probably due to a mismatch between internal circadian rhythms and work schedule obligations in early sleepers [ 73 ]. We have shown that later sleep timing characteristics are associated with taste perception, specifically a lower bitter taste perception and TAS2R38-rs713598, and with a higher taste intensity for salty and sour tastes.…”
Section: Discussionmentioning
confidence: 99%
“…In our work on sleep and eating patterns, we found a modulating effect only on the midpoint of sleep for all three genes. The midpoint of sleep was correlated with the dim light melatonin onset (DLMO), a marker of the internal circadian phase and the onset of the biological night [ 72 , 85 , 86 ]. Eating closer or after DLMO was related to higher body fat [ 86 ] and glucose levels [ 87 ], possibly due to a prolonged glucose spike during the night [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…91,92 Furthermore, having a later midpoint of sleep has been linked to increased insulin resistance as measured with HOMA-IR, 93,94 and increased risk of type 2 diabetes. 95 In treatment-naive individuals with type 2 diabetes, higher fasting glucose levels were associated with a later bedtime. 93 Conversely, another large study found no association between chronotype and HbA1c levels in patients with type 2 diabetes, 96 although the investigators did not control for diabetes medication.…”
Section: Desynchrony Due To Mistimed Sleepmentioning
confidence: 99%
“…A few studies have noted these issues and further analyzed the possible association between different sleep patterns and T2DM. For example, Zhai et al found that compared to those with an intermediate chronotype and 7-8 h of night sleep duration, individuals with a night chronotype and >9 h of night sleep duration had the highest risk of T2DM [18]. A meta-analysis showed that short objective sleep duration (<6 h) was significantly associated with T2DM only in the presence of insomnia symptoms [19].…”
Section: Introductionmentioning
confidence: 99%